Delving into Female Adolescents Leadership Experiences in the Midst of Leading Service Learning Engagements: A Qualitative Case Study - Michael, Heather; Mitton-Kükner, Jennifer (Alberta Journal of Educational Research, 2017)
The purpose of this work is to explore the experiences of four adolescent females who assumed leadership roles in service learning projects, in order to understand more about how those projects inspired and informed their understanding of themselves as leaders in the school and community. What became clear through this study is that age and gender played largely into participants’ understanding of leadership. It also became evident that adolescent females need opportunities to practice their leadership skills and that service learning projects have the potential to create such occasions. L’objectif de ce travail est d’explorer les expériences de quatre adolescentes qui ont assumé des rôles de leadership dans le contexte de projets d’apprentissage par le service, et d’en tirer des connaissances sur la mesure dans laquelle ces projets les ont inspirées et ont façonné leur identité de chef au sein de l’école et de la communauté. Les résultats indiquent que l’âge et le sexe ont joué un rôle significatif dans leur compréhension du leadership. Ils révèlent également que les adolescentes ont besoin d’occasion de pratiquer leurs compétences en leadership et que les projets d’apprentissage par le service présentent le potentiel de fournir de telles occasions.